2017
DOI: 10.1186/s12916-017-0858-9
|View full text |Cite
|
Sign up to set email alerts
|

Expedited Partner Therapy (EPT) increases the frequency of partner notification among MSM in Lima, Peru: a pilot randomized controlled trial

Abstract: BackgroundExpedited Partner Therapy (EPT) has been shown to improve treatment outcomes among heterosexual partners of individuals with curable sexually transmitted infections (STIs). Although the use of EPT with men who have sex with men (MSM) has been debated, due to the potential for missed opportunities to diagnose unidentified cases of HIV and syphilis infection in symptomatic partners, increases in partner notification (PN) resulting from use of EPT may promote testing and treatment of otherwise unidentif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…We noted signs and symptoms of primary syphilis in 36 individuals, whereas secondary infection was identified in 22 others. Of 479 MSM and TW with latent infection and positive RPR and MHA-TP assays, 74 were diagnosed with a previously treated infection that did not require additional treatment, 64 did not return for their results, and 29 were enrolled in a concomitant trial of expedited partner therapy for gonorrhea or chlamydia infection [ 42 ]. We enrolled 370 MSM or TW with recently diagnosed syphilis infection and randomly assigned each to one of the following four arms: (1) standard counseling or control (arm 1; N=94), (2) referral cards (arm 2; N=97), (3) Web-based PN (arm 3; N=95), or (4) combination Web-based PN and referral cards (arm 4; N=84).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We noted signs and symptoms of primary syphilis in 36 individuals, whereas secondary infection was identified in 22 others. Of 479 MSM and TW with latent infection and positive RPR and MHA-TP assays, 74 were diagnosed with a previously treated infection that did not require additional treatment, 64 did not return for their results, and 29 were enrolled in a concomitant trial of expedited partner therapy for gonorrhea or chlamydia infection [ 42 ]. We enrolled 370 MSM or TW with recently diagnosed syphilis infection and randomly assigned each to one of the following four arms: (1) standard counseling or control (arm 1; N=94), (2) referral cards (arm 2; N=97), (3) Web-based PN (arm 3; N=95), or (4) combination Web-based PN and referral cards (arm 4; N=84).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the dissipation of the intervention effect observed as we progressed through the partner management cascade might reflect the participants’ inability to follow up on their notification messages, particularly the ones sent to casual partners through an anonymous, Web-based system. The lack of an observed effect on downstream outcomes indicates the need for additional interventions to support partner management outcomes throughout the partner management cascade, beginning with notification and culminating with a linkage to and retention in HIV or STI care [ 42 ]. While the preliminary research on potential responses to hypothetical anonymous notification messages among MSM in Peru indicated that the recipients would be motivated to seek medical attention after receiving an anonymous message, data from the United States have suggested otherwise, and this study too did not collect any partner-confirmed information on postnotification behavior [ 33 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data support prior feasibility data about using PDPT with GBM. In a pilot study, 83.1% of GBM randomised to the PDPT arm notified at least one recent sexual partner and more than half (53.5%) notified all recent partners 13. Secondary distribution of HIVST kits is also acceptable and feasible among GBM in the USA,14 15 suggesting the integration of these two components is practical in real-world settings.…”
Section: Discussionmentioning
confidence: 99%
“…The dissipation of intervention effect observed as we progressed through the partner management cascade may also reflect participants' inability to follow-up on their notification messages, particularly ones sent to casual partners through an anonymous, web-based system. The lack of an observed effect on downstream outcomes indicates the need for additional interventions to support partner management outcomes throughout the partner management cascade, beginning with notification, and culminating with linkage to and retention in HIV/STI care (45). While preliminary research on potential responses to hypothetical anonymous notification messages among MSM in Peru indicated that recipients would be motivated to seek medical attention after receiving an anonymous message, data from the U.S. has suggested the opposite, and our study did not collect any partner-confirmed information on post-notification behavior (30,46).…”
Section: Discussionmentioning
confidence: 99%